Energy-Aware Hierarchical Topology Control for Wireless Sensor Networks with Energy-Harvesting Nodes - Ikjune Yoon; Dong Kun Noh; Heonshik Shin (International Journal of Distributed Sensor Networks)
The nodes in a wireless sensor network (WSN) are often clustered to improve the efficiency of data transmission, but this can cause an imbalance in the energy available at each node. This impairs the transmission capability of some nodes and hence reduces network connectivity. This imbalance worsens as nodes become defunct. We propose a multilayer topology for long-term hybrid WSNs which contain both battery-powered and energy-harvesting nodes. Each node periodically selects its own layer, depending on the energy it has available, in order to balance energy levels and maintain network connectivity. Simulations show that this scheme improves the delivery of data across a WSN.